The expression of calretinin and cytokeratins in canine acanthomatous ameloblastoma and oral squamous cell carcinoma. (18th September 2012) - Fulton, A.; Arzi, B.; Murphy, B.; Naydan, D. K.; Verstraete, F. J. M.
Abstract Oral squamous cell carcinoma (OSCC) and canine acanthomatous ameloblastoma (CAA) represent two epithelium‐derived neoplasms that affect the oral cavity of dogs. The expression of cytokeratins (CKs) and calretinin has been previously established in the canine tooth bud and odontogenic tumours. The aim of this study was to characterize the CK and calretinin expression profile of OSCC in comparison to CAA and canine tooth bud tissues. Samples from 15 OSCC and 15 CAA cases, as well as 6 tooth buds and 2 normal gingival tissues were examined. OSCC CK expression was consistent with the CK expression profile of CAA and canine tooth bud tissue. Calretinin was positively expressed in 10 of 15 OSCC cases, with 5 cases demonstrating high staining intensity. Only 2 of 15 CAA cases demonstrated mild‐moderate staining intensity. The statistically significant difference in staining pattern and intensity of calretinin in OSCC and CAA can help distinguish between these two tumour types.